METAL ACCUMULATION ASSESSMENT IN PLANTS AND SOIL AT KUDUKU MINING SITE, NASARAWA, NIGERIA - Ilyas, S.; Sabo, A.; Akomolafe, G. F.; Mustafa, Y. S. (FUDMA JOURNAL OF SCIENCES, 2023)
Mining activities usually alter ecosystems through the disruption of the vegetations and the deposition of potentially toxic elements. This study investigated the soil pollution level and evaluated the phytoremediation potential of some native plant species on a mining site at Kuduku, which is located in Keana local government area of Nasarawa State. Plant samples and associated soils were collected from the mining site and analyzed for the presence of metals such as Pb, Cd, Cr and Mn. The Bioconcentration factor (BCF), Translocation Factor (TF) and Enrichment Factor (EF) were also analyzed. They were generally higher concentration of the heavy metal in most of the plants than in soils which indicates the ability of the plant to tolerate and accumulate these metals. Most of the investigated plants have potentials of been phytostabilizers or phytoextractors. Lead recorded the following plants as phytostabilizers; Acalypha indica. Copper had the following plants as good phytoextractors; Sida acuta, Fumaria parviflora, Triumfetta rhomboidea, Acalypha indica and Ageratum conyzoides. For Manganese, the phytoextractors includes: Calopogonium mucunoides, Fumaria parviflora, Ageratum conyzoides while phytostablizers includes: Triumfetta rhomboidea and Sida acuta. Most of the investigated plants had an enrichment factor (EF) greater than one which also emphasizes on the extent of metal uptake by the plants. For the majority of the plants investigated, their EF was greater than one except in few cases.